Electronic Commerce Technology Adoption at the Scientific and Industrial Research and Development Centre - Rashama, Cosmas; Mungwena, Wilson; Damba, Tonderai (Scientific Research Publishing, 2013)
This paper focuses on the level of adoption of E-Commerce Technology at the Scientific and Industrial Research and Development Centre (SIRDC), a Zimbabwean organization established by an act of parliament, with a mandate to develop, adopt and adapt new technologies for the benefit of Zimbabwean companies and organizations. The study was done in 2004 and the findings reviewed in 2012 with similar results. The objective of the study was to establish whether E-commerce technology adoption would result in the organization being more efficient and effective in delivering its mandate and then establish the level of adoption of the technology at the centre using abstraction and a questionnaire survey. Abstraction results showed that organizations which had fully embraced the technology were more efficient and effective while the survey revealed that the centre had partially adopted the technology. It was recommended that the centre should fully embrace the technology and market it to other organizations as per its mandate.
Keywords: Electronic Commerce; Non-Repudiation; Internet; Intranet; Extranet